Human security and non-citizens - Edwards, Alice (ed.) (Delhi, 2010)
The past decades have seen enormous changes in our perceptions of 'security', the causes of insecurity and the measures adopted to address them. Threats of terrorism and the impacts of globalisation and mass migration have shaped our identities, politics and world views. This volume of essays analyses these shifts in thinking and, in particular, critically engages with the concept of 'human security' from legal, international relations and human rights perspectives. Contributors consider the special circumstances of non-citizens, such as refugees, migrants, and displaced and stateless persons, and assess whether, conceptually and practically, 'human security' helps to address the multiple challenges they face.
Keywords: Refugees-Legal status, Law